2022
DOI: 10.1039/d2tc01289h
|View full text |Cite
|
Sign up to set email alerts
|

Employing three-blade propeller lanthanide complexes as molecular luminescent thermometers: study of temperature sensing through a concerted experimental/theory approach

Abstract: We report the synthesis, structures, magnetic and luminescent properties of a series of three-blade propeller homoleptic lanthanide complexes [LnL3](ClO4)3·H2O·2MeCN (Ln = Eu (1), Tb (2), Dy (3), Er (4), Yb...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…After 200 K, as the temperature increases, the emission intensity of the Yb III –PDMS system increases, as previously observed by us 22 for the free-standing complex, suggesting that the energy transfer from the ligand to Yb III is thermally assisted from then on. This thermally dependent ligand to Ln III energy transfer has already been reported for Eu III and Tb III complexes, 34,35 yet, contrary to such systems, the energy transfer pathways in Yb III complexes are not so well elucidated in the literature due to the large energetic mismatch between Yb III excited states and ligand donor states. For instance, Kasprzycka and coworkers 36 recently showed that in a Yb III complex with N-phosphorylated sulfonamide ligands, the S 1 → LMCT → T 1 → Yb III path displays larger contribution than the S 1 → T 1 → Yb III one.…”
Section: Resultsmentioning
confidence: 61%
“…After 200 K, as the temperature increases, the emission intensity of the Yb III –PDMS system increases, as previously observed by us 22 for the free-standing complex, suggesting that the energy transfer from the ligand to Yb III is thermally assisted from then on. This thermally dependent ligand to Ln III energy transfer has already been reported for Eu III and Tb III complexes, 34,35 yet, contrary to such systems, the energy transfer pathways in Yb III complexes are not so well elucidated in the literature due to the large energetic mismatch between Yb III excited states and ligand donor states. For instance, Kasprzycka and coworkers 36 recently showed that in a Yb III complex with N-phosphorylated sulfonamide ligands, the S 1 → LMCT → T 1 → Yb III path displays larger contribution than the S 1 → T 1 → Yb III one.…”
Section: Resultsmentioning
confidence: 61%
“…Sensitivity values Sr from 3 to 16% K –1 within the 77–150 K range were obtained (Figure S10b). The PU-C x materials thus constitute a relevant example of ratiometric luminescence thermometers of different types compared with the more common lanthanide-based materials, for which the two emissive bands are from different emitters . Compared to powdered compounds, PU-C x functional polymers can additionally be specifically designed for thermometry applications.…”
Section: Resultsmentioning
confidence: 99%
“…Although the calculation of the ligand-to-Ln 3+ transfer rates is out of the scope of the present work, we stress that the temperature dependence of the Eu 3+ and Tb 3+ emissions within the di-ureasil hybrid matrix was already theoretically rationalized. [45,[53][54][55] The temporal dynamics of the luminescence of dU6EuTb and its relation with the detection parameters (W and D) will be addressed in future works.…”
Section: Implementing Time-resolved Spectroscopymentioning
confidence: 99%
“…[56,57] Furthermore, the thermal behavior of I Tb and I Eu emissions can be also forecasted. [45,[53][54][55] For example, Ramalho et al successfully estimated I Tb and I Eu for similar organic-inorganic hybrids compounds with 2-thenoyltrifluoroacetone and salicylic acid as main ligands. [45] Recognizing that this device was not designed to perform rapid switches between low-and high-pass filters, we should however stress that this time can be modeled by the physical properties of the material such as the mass and the thermal capacity.…”
Section: Defining the Transfer Function Of The All-photonic Molecular...mentioning
confidence: 99%